Development of Mother Tongue Based Competences Outside the Classroom - Ph. D. B. Boltayeva; L. Shakarova (Scientific Trends, 2023)
This article discusses the development of basic competencies in extracurricular activities in primary education.
Keywords: competence, basic competence, extracurricular activities, national and universal competence.